Migraine in men – differences in phenotype and treatment patterns: results from the Migraine in Poland cross-sectional national survey - Marta Waliszewska-Prosół; Karol Marschollek; Sławomir Budrewicz; Mieszko Więckiewicz; Magdalena Nowaczewska; Marcin Straburzyński (The Journal of Headache and Pain)
Abstract Background The ‘Migraine in Poland’ study is a large-scale nationwide cross-sectional online survey that assessed symptomatology, consulting, diagnosis, treatment, and burden of migraine in Poland, conducted from August 2021 to June 2022. The purpose of this paper is to define migraine phenotype and patterns of care for Polish men. Methods Participants were recruited through various channels, primarily targeting individuals experiencing headaches. The questionnaire evaluated healthcare system utilization, headache features, history of diagnosis, comorbidities, burden, as well as the use of acute or preventive treatment. The survey included questions that allowed for diagnosis according to the International Classification of Headache Disorders-3. Results 3225 individuals aged 13 to 80 (mean age 38.9) responded to the survey (87.1% were women). Migraine without aura diagnosis was confirmed in 1679 (52.7%) of subjects, and this group was included in further analysis. The current study group consisted of 244 men (14.6%) and 1431 women (85.4%). Men tended to experience fewer types of headaches compared to women (p < 0.001) and were significantly less likely to report visual and sensory symptoms accompanying the worst headache than women (p < 0.001). Premonitory symptoms preceding the onset of headache were more likely, and the time required to return to normal functioning was longer in men than in women (median 24 and 10 h, respectively; p < 0.001). The use of acute treatment was significantly higher in men, regarding both physician-prescribed medications (80.3% vs. 69.3%; p < 0.001) and over-the-counter medications (77% vs. 52.2%; p < 0.001), as well as natural-based or alternative remedies (43% vs. 15.4%; p < 0.001). Men were more likely to use combination drugs (66% vs. 57.9%; p = 0.017) and often fulfilled the criteria for medication overuse (29.5% vs. 22%; p = 0.01). Prophylactic treatment was less frequently used in men (21.7% vs. 38%; p < 0.001). Men reported spending more money on medications monthly than women (p < 0.001). Both on the MIDAS (p < 0.001) and PHQ-9 (p = 0.002) scales, men scored lower than women. Conclusions Our study confirms the existence of significant gender differences in the course of migraine, both in terms of clinical characteristics of the disease and patterns related to health behaviors and access to medical care.